2014
DOI: 10.1007/s11845-014-1233-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, continence and frequency of pouchitis following laparoscopic versus open colectomy and ileal pouch-anal anastomosis: an Irish perspective

Abstract: Ileal pouch-anal anastomosis is a successful and well-tolerated procedure with 94 % of patients opting to have the surgery again. Preliminary results do not show any significant difference in the incidence of pouchitis following laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The high frequency in our population (48%) was similar to that reported in other countries such as United States [23], Belgium [24], Irish population [25] and Puerto Rico [28]. This data differs from other countries where 34% was reported in Scotland [26] and 21.7% in Brazil [27], and differ widely from China (5.3%) [29] and Japan (10%) [30].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The high frequency in our population (48%) was similar to that reported in other countries such as United States [23], Belgium [24], Irish population [25] and Puerto Rico [28]. This data differs from other countries where 34% was reported in Scotland [26] and 21.7% in Brazil [27], and differ widely from China (5.3%) [29] and Japan (10%) [30].…”
Section: Discussionsupporting
confidence: 86%
“…In other regions like Belgium, pouchitis is reported in 46% of the patients [24]. In the Irish population, on the other hand, pouchitis appears in 48.5% of the cases [25], and Scotland data report pouchitis in 34% of the patients [26]. Talking about Latin American countries, there are Brazilian data that report pouchitis in 21.7% of the patients [27] and a study of the Puerto Rico experience that reports pouchitis in 44% of them [28].…”
Section: Introductionmentioning
confidence: 99%
“…The median age at operation time was 11 years (4-16 years). The median weight was 30 kg (15 kg-58 kg), and the median body mass index (BMI) was 17 (range [13][14][15][16][17][18][19][20][21][22]. The median operating time was 180 minutes (range 120-240 minutes).…”
Section: Resultsmentioning
confidence: 99%
“…In a study of adults, most of the patients had a Wexner Score of 0, indicating no problems with continence after their pouch surgery, and 94% of the patients reported that they would choose the surgery over medical treatment because IPAA is a successful and well-tolerated procedure (20).…”
Section: Discussionmentioning
confidence: 99%
“…German and an Irish study with 10-year follow-up found favorable quality of life after IPAA surgery [54,55] . Nutritional difficulties, bowel movement problems, as well as daily and nighttime incontinence were found in both groups.…”
Section: Discussionmentioning
confidence: 94%